Βιβλιοκρισία: A. J. QUIROGA PUERTAS, The Dynamics of Rhetorical Performances in Late Antiquity. London; New York: Routledge, 2019 - ΚΑΡΛΑ Γραμματική (Byzantina Symmeikta, 2020)
Βιβλιοκρισία: ALBERTO J. QUIROGA PUERTAS, The Dynamics of Rhetorical Performances in Late Antiquity. London; New York: Routledge, 2019